PENGARUH BUDAYA KERJA TERHADAP KINERJA SUMBER DAYA MANUSIA BANK SYARIAH INDONESIA CABANG BANDUNG SUNIARAJA - Zakaria, Yogi Aditya; Mulyana, Dadang; Nurrahman, Arif (Program Studi Ekonomi Syariah Universitas Muhammadiyah Bandung, 2025)
The quality of human resource performance plays a very important role in the success of an organization in achieving its goals. Therefore, organizations are expected to continue to improve and develop the performance of their human resources. In an effort to empower employees to produce professional and high integrity human resources, organizations need to apply consistent standards. The standard is an organizational culture that provides systematic guidance to employees to improve their performance for the benefit of the organization. This study aims to determine the effect and how much influence between work culture on human resource performance. This research adopts quantitative methods. The population in this study amounted to 39 people where the sample taken was also 39 people in Bank Syariah Indonesia then the data collection technique used was the field method by distributing questionnaires to all employees and the analysis method in this study used simple linear regression analysis.